Discrimination contours for the perception of head-centred velocity - Champion, Rebecca A. (2010)
There is little direct psychophysical evidence that the visual system contains mechanisms tuned to head-centred velocity when observers make a smooth pursuit eye movement. Much of the evidence is implicit, relying on measurements of bias (e.g. matching and nulling). We therefore measured discrimination contours in a space dimensioned by pursuit target motion and relative motion between target and background. Within this space, lines of constant head-centred motion are parallel to the main negative diagonal, so judgements dominated by mechanisms that combine individual components should produce contours with a similar orientation. Conversely, contours oriented parallel to the cardinal axes of the space indicate judgements based on individual components. The results provided evidence for mechanisms tuned to head-centred velocity – discrimination ellipses were significantly oriented away from the cardinal axes, towards the main negative diagonal. However, ellipse orientation was considerably less steep than predicted by a pure combination of components. This suggests observers used a mixture of two strategies across trials, one based on individual components and another based on their sum. We provide a model that simulates this type of behaviour and is able to reproduce the ellipse orientations we found.